2000
DOI: 10.1128/cdli.7.2.241-244.2000
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies in Patients with Chronic Hepatitis C Virus Infection: Characterization in Relation to Antiphospholipid Syndrome

Abstract: The antiphospholipid syndrome (APS) is usually defined by the association of clinical manifestations that comprise venous and/or arterial thrombosis, recurrent fetal losses, and thrombocytopenia, along with the presence of anticardiolipin (aCL) antibodies and/or lupus anticoagulant. Various infectious diseases can induce aCL; however, these antibodies are not usually associated with thrombotic events, as happens with autoimmune diseases, in which these antibodies need the presence of ␤ 2 -glycoprotein I. Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 26 publications
2
45
1
Order By: Relevance
“…The frequency of organ-specific autoantibodies in HCV patients included in our study is significantly lower than that of the non-organ specific autoantibodies, which could explain the systemic nature of the clinical syndromes associated with patients with HCV, which include rheumatic manifestations and systemic vasculitis, as suggested by other studies. 24,26,34,35 The prevalence of ACA among patients with chronic HCV has been investigated by other groups, who describe an ACA frequency among HCV patients ranging from 3-22%. 11,35,36 Our results fell within this range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of organ-specific autoantibodies in HCV patients included in our study is significantly lower than that of the non-organ specific autoantibodies, which could explain the systemic nature of the clinical syndromes associated with patients with HCV, which include rheumatic manifestations and systemic vasculitis, as suggested by other studies. 24,26,34,35 The prevalence of ACA among patients with chronic HCV has been investigated by other groups, who describe an ACA frequency among HCV patients ranging from 3-22%. 11,35,36 Our results fell within this range.…”
Section: Discussionmentioning
confidence: 99%
“…24,26,34,35 The prevalence of ACA among patients with chronic HCV has been investigated by other groups, who describe an ACA frequency among HCV patients ranging from 3-22%. 11,35,36 Our results fell within this range. The wide range of ACA reported by different groups may be explained by differences in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…8OHdG is well recognized as oxidatively generated DNA damage [80], implying that the emergence of anti-cardiolipin was associated with oxidative stress in those patients. However, none of the CH-C patients seropositive for anticardiolipin fulfilled the category for anti-phospholipid syndrome [79,[81][82][83][84]. It is of interest that anti-cardiolipin in patients with CH-C were in generally low titers, and were not associated with antibodies to 2-glycoprotein-I.…”
Section: ) Clinical Significance Of Autoimmunity In Liver Diseases Amentioning
confidence: 99%
“…Antibodies to oxidatively modified autoantigens were also trapped in the sera of patients with NAFLD and chronic hepatitis C (CH-C). Titers of malondialdehyde (MDA)-adducted NAFLD correlation with hepatic fibrosis [73] anti-oxLDL oxLDL HCV correlation with hepatic steatosis [75] anti-SOD SOD AIH false-positivity for anti-HCV [78] anti-cardiolipin cardiolipin HCV correlation with oxidative stress [79] HCV higher prevalence of portal hypertension [86] HCV lack in the symptoms for anti-phospholipid syndrome [79,[81][82][83][84] HCV concurrent oral lichen planus [87] HCV concurrent mixed cryoglobulin [88] NASH N/A [79] AIH Indicator for more advanced liver fibrosis [89] PBC, PSC indicator for more advanced liver fibrosis [90] anti-CYP2E1 CYP2E1 halothene-induced hepatitis specific to IgG4 type of anti-CYP2E1 [101] alcoholic liver cirrhosis N/A [95,96] AIH N/A [97][98][99] HCV indicator for more severe necroinflammation [97,102] anti-HSP HSP65 AIH molecular mimicry between HSP and SOD [105] HSP70 PBC indicator for disease activity [106] HSP70 HCV inverse correlation with diseae-activity [108] human serum albumin (HSA) were elevated in CH-C patients with severe hepatic steatosis [72]. To the contrary, an increase in titers of antibodies to MDA-HSA was independently associated with the progression of liver fibrosis in patients with NAFLD [73].…”
Section: ) Clinical Significance Of Autoimmunity In Liver Diseases Amentioning
confidence: 99%
“…HCV infection may lead to autoimmune response. It has been reported that chronically infected HCV patients possess anti-smooth muscle antibodies, rheumatoid factor, anti-liver-kidney-microsomal antibodies, anticardiolipin antibodies (ACA), and low titers of antinuclear antibodies (2). Interferon treatment of HCV infection may precipitate or exacerbate the associated autoimmune disease (3).…”
Section: Introductionmentioning
confidence: 99%